The tox is in the detail: technical fundamentals for designing, performing, and interpreting experiments on toxicity of microplastics and associated substances - Heinrich, Patrick; Hanslik, Lisa; Kämmer, Nadine; Braunbeck, Thomas (Environmental science and pollution research, 2020)
Over the last 10 years, there has been a plethora of experimental studies estimating the potential of microplastic particles (MPs) to exert toxic effects in the environment, many specifically focusing on their postulated capacity to enhance the transfer of environmental pollutants into organisms after ingestion. Obviously, there is little to no consensus on appropriate experimental design, which is mainly owing to the novelty, the interdisciplinarity of the subject, and the complexity of parameters involved. This results in fundamental discrepancies regarding the materials applied, the approach for spiking MPs with pollutants, and the exact exposure scenario. Aiming for a non-chemist audience and providing illustrative, representative, and comparative examples, this review first outlines the theoretical essentials of processes involved in sorption. Also, it discusses the implications for designing experimental approaches using MPs and interpreting the results obtained under consideration of their relevance for environmental conditions. It may help to improve the interpretation of studies on MP toxicity already published, while also calling experimenters’ attention to various aspects important to consider when designing and performing environmentally relevant experiments with MPs.